PENGARUH MANAJEMEN LABA, CORPORATE GOVERNANCE, DAN INTENSITAS MODAL TERHADAP AGRESIVITAS PAJAK PERUSAHAAN (Studi Empiris pada Perusahaan Property dan Real Estate yang Terdaftar di BEI Periode Tahun 2010-2014) - Shelly Novitasari; Vince Ratnawati; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine and analyze the effect of earnings management, Corporate Governance with proxy (managerial ownership, institutional ownership, independent commissioner, and the meeting intensity of the audit committee) and capital intensity against corporate tax aggressive. The dependent variable in this study is tax aggressive are measured using Cash Effective Tax Rate (CETR). The population in this study is the property and real estate companies listed on Indonesian Stock Exchange (BEI) 2010-2014. The sample was determined by the purposive sampling method and obtain 26 companies. Type of data used was secondary data obtained from www.idx.co.id or ICAMEL. Data analysis conducted with multiple linear regression model with help of software SPSS version 22,0. Of the result of the testing that has been done, the partial regression test (t test) showed that the independent variables earnings management, institutional ownership, and independent commissioner which has a significant effect on tax aggressive. Meanwhile managerial ownership, the meeting intensity of the audit committee, and capital intensity has no effect on tax aggressive. Based on total adjusted R-square result proved that variables of earnings management, managerial ownership, institutional ownership, independent commissioner, the meeting intensity of the audit committee, and capital intensity on tax aggressive results of 17,3% while the rest of 82,7% were affected by other variables that were not performed in this studyKeywords: Earnings Management, Corporate Governance, Capital intensity, and Tax aggressive